Analisa Biaya Operasional Kendaraan Bus Angkutan Kota Jurusan Palangka Raya-Pangkalan Bun - Muhammad Gemilang P. Utama; Nirwana Puspasari (Media Ilmiah Teknik Sipil, 2020)
Transportation is an important role in aspects of social economic and cultural activities. Based on the distribution of passenger traffic in and out of the land transportation, the Bus fleet majoring in Palangkaraya-Pangkalan Bun is the most desirable transportation service because travel times are faster and more efficient. The research objective is to determine the magnitude of operational costs for public transportation vehicles Palangka Raya-Pangkalan Bun. The method of collecting passenger data and bus fleet data is a non-random sampling method. Primary data in the form of vehicle operating costs are analyzed by the method of cost per kilometer approach for each vehicle, revenue is analyzed by the method of approaching the average amount of revenue of the company per year and subtracted by total vehicle operating costs per kilometer, rates are analyzed by the method of adding the fixed cost components, costs variable and overhead costs in units per passenger and Fare Box Ratio (FBR) are analyzed using the method of comparing the value of Vehicle Operating Costs per year with annual income. From the results of the study, the amount of Operational Cost needs is spent at 81% of annual income. With a Factor Load calculation of 12 passengers per Trip over the past three years. The fare incurred for ticket purchase per one time departure is Rp 130,000.00 with a Fare Box Ratio (FBR) of 123% so that it can be categorized as a profit